Nitrogen-doped carbon@TiO2 double-shelled hollow spheres as an electrochemical sensor for simultaneous determination of dopamine and paracetamol in human serum and saliva - Hui Yang; Gongxun Cao; Yongjun Huang; Ye Lin; Fengying Zheng; Luxiu Lin; Fengjiao Liu; Shunxing Li (Elsevier, 2022)
As the most commonly used antipyretic and analgesic drug, paracetamol (PA) coexists with neurotransmitter dopamine (DA) in real biological samples. Their simultaneous determination is extremely important for human health, but they also interfere with each other. In order to improve the conductivity, adsorption affinity, sensitivity, and selectivity of TiO2-based electrochemical sensor, N-doped carbon@TiO2 double-shelled hollow sphere (H-C/N@TiO2) is designed and synthesized by simple alcoholic and hydrothermal method, using polystyrene sphere (PS) as a template. Meanwhile, TiO2 hollow spheres (H-TiO2) or N-doped carbon hollow spheres (H-C/N) are also prepared by the same method. H-C/N@TiO2 has good conductivity, charge separation, and the highly enhanced and stable current responses for the detection of PA and DA. The detection limit and linear range are 50.0 nmol/L and 0.3-50 μmol/L for PA, 40.0 nmol/L and 0.3-50 μmol/L for DA, respectively, which are better than those of carbon-based sensors. Moreover, this electrochemical sensor, with high selectivity, strong anti-interference, high reliability, and long time durability, can be used for the simultaneous detection of PA and DA in human blood serum and saliva. The high electrochemical performance of H-C/N@TiO2 is attributed to the multi-functional combination of different layers, because of good conductivity, absorption and electrons transfer ability from in-situ N-doped carbon and electrocatalytic activity from TiO2.